2014
DOI: 10.1080/09593330.2014.924566
|View full text |Cite
|
Sign up to set email alerts
|

The use of chlorine dioxide for the inactivation of copepod zooplankton in drinking water treatment

Abstract: The presence of zooplankton in drinking water treatment system may cause a negative effect on the aesthetic value of drinking water and may also increase the threat to human health due to they being the carriers of bacteria. Very little research has been done on the effects of copepod inactivation and the mechanisms involved in this process. In a series of bench-scale experiments we used a response surface method to assess the sensitivity of copepod to inactivation when chlorine dioxide (ClO₂) was used as a di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…All zooplankton individuals remained alive throughout all the treatment steps. The fluorescence-quenching rate of E. coli-EGFP stabilized after 30 min chlorination because of reduced viability of L. sinensis as a result of chlorine oxidation (Lin et al, 2014a, b). The intake of disinfectant by grazing thus plays an important role in the inactivation of internalized microorganisms in L. sinensis.…”
Section: Egfp Fluorescence In E Colimentioning
confidence: 99%
See 1 more Smart Citation
“…All zooplankton individuals remained alive throughout all the treatment steps. The fluorescence-quenching rate of E. coli-EGFP stabilized after 30 min chlorination because of reduced viability of L. sinensis as a result of chlorine oxidation (Lin et al, 2014a, b). The intake of disinfectant by grazing thus plays an important role in the inactivation of internalized microorganisms in L. sinensis.…”
Section: Egfp Fluorescence In E Colimentioning
confidence: 99%
“…Higher zooplankton colonization have been documented in BAC filter (Lin et al, 2014a, b). BAC filters are associated with the accumulation of both biological and non-biological particles that provide a rich food source for zooplankton.…”
Section: Introductionmentioning
confidence: 98%
“…A combination of chlorine and chloramine disinfection method was reported, intracellular organic matter of Cyclops was well controlled under a 10 mg/L concentration of both chlorine and chloramine (Sun et al 2016 ). Researchers suggested that chlorine dioxide had stronger effect than chlorine in general (Zhao et al 2007 ; Lin et al 2014 ; Nie et al 2016 ). After 30 min contact, 100% of water fleas were inactivated at 1.0 mg/L chlorine dioxide, with the same contact time, the same inactivation rate required a concentration of 2.0 mg/L of liquid chlorine (Cui et al 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies indicated that copepods can often infiltrate sedimentation and filtration tanks because of their high mobility, causing the proliferation of these species and reaching a density up to 600 individuals/L (Xu et al 2007;Su et al 2009). The solid chitinous carapace of copepods is highly resistant against chemicals used in disinfection process before delivery (Lin et al 2014), even 5 times of current chlorine and ozone doses had no long-term inhibitory effect on oocysts development in finished water (Dhillon et al 2010;Hardin et al 2010). Since 1995, a series of Cyclops leakage in water supply network were reported in Harbin and Shijiazhuang, China (Cui et al 2002;Xing et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Calibration data are obtained from the literature and two experiments in the laboratory. Data on the ingestion rate, the assimilation efficiencies of zooplankton and benthos, and the respiratory cost for grazing by zooplankton are obtained from the literature 51 . The inhibitory rate of chlorine on phytoplankton and zooplankton is obtained from the literature 52 , 53 .…”
Section: Methodsmentioning
confidence: 99%